"Vibrational Bonding": A New Type of Chemical Bond is Discovered. (March 2015) - Rhodes, Christopher J.; Macrae, Roderick M.
A long-sought but elusive new type of chemical bond, occurring on a minimum-free, purely repulsive potential energy surface, has recently been convincingly shown to be possible on the basis of high-level quantum-chemical calculations. This type of bond, termed a vibrational bond, forms because the total energy, including the dynamical energy of the nuclei, is lower than the total energy of the dissociated products, including their vibrational zero-point energy. For this to be the case, the ZPE of the product molecule must be very high, which is ensured by replacing a conventional hydrogen atom with its light isotope muonium (Mu, mass = 1/9 u) in the system Br – H – Br, a natural transition state in the reaction between Br and HBr. A paramagnetic species observed in the reaction Mu + Br2 has been proposed as a first experimental sighting of this species, but definitive identification remains challenging.